Inter and intra-host variability of hepatitis C virus genotype 1a hypervariable envelope coding domains followed for a 4-11 year of human immunodeficiency virus coinfection and highly active antiretroviral therapy - Sede, Mariano Miguel (2014)
The evolution of hepatitis C virus (HCV) quasispecies in patients with HIV-1 coinfection is not fully understood. The HCV-1a quasispecies heterogeneity was analyzed at inter and intra-host levels along 7.6 years in 21 coinfected patients that showed different virological and immunological responses to highly active antiretroviral therapy (HAART). Two to nine serial samples were subjected to direct and clonal sequence analyses of the envelope glycoprotein 2 (E2) gene. E2-based phylogenies, intra-host HCV evolution and evolutionary rates, as well as dynamics of the quasispecies heterogeneity parameters were evaluated. Bayesian coalescent phylogenies indicated complex evolutionary histories, revealing some viral lineages that persisted along the follow up and others that were detectable at a single or some sampling times, suggesting the occurrence of emergence-extinction cycles. HCV quasispecies underwent very rapid evolution in HAART-treated patients (~3.1 × 10(-2) sub/site/year) following the recovery of the host immunocompetence irrespectively of the virological response to HAART.